An Orphan LuxR Homolog of Sinorhizobium meliloti Affects Stress Adaptation and Competition for Nodulation - Patankar, Arati V. (American Society for Microbiology (ASM), 2009)
The Sin/ExpR quorum-sensing system of Sinorhizobium meliloti plays an important role in the symbiotic association with its host plant, Medicago sativa. The LuxR-type response regulators of the Sin system include the synthase (SinI)-associated SinR and the orphan regulator ExpR. Interestingly, the S. meliloti Rm1021 genome codes for four additional putative orphan LuxR homologs whose regulatory roles remain to be identified. These response regulators contain the characteristic domains of the LuxR family of proteins, which include an N-terminal autoinducer/response regulatory domain and a C-terminal helix-turn-helix domain. This study elucidates the regulatory role of one of the orphan LuxR-type response regulators, NesR. Through expression and phenotypic analyses, nesR was determined to affect the active methyl cycle of S. meliloti. Moreover, nesR was shown to influence nutritional and stress response activities in S. meliloti. Finally, the nesR mutant was deficient in competing with the wild-type strain for plant nodulation. Taken together, these results suggest that NesR potentially contributes to the adaptability of S. meliloti when it encounters challenges such as high osmolarity, nutrient starvation, and/or competition for nodulation, thus increasing its chances for survival in the stressful rhizosphere.